RISK ANALYSIS OF STUNTING INCIDENCE OF TODDLERS IN MAJENE REGENCY, WEST SULAWESI - RYADINENCY, RESTY; MISNAWATI, ANDI (International Journal of Multidisciplinary Research and Studies, 2022)
Background: Stunting is a condition of failure to grow in toddlers due to chronic malnutrition, especially during the first 1,000 days of life. Less protein and zinc intake, history of low birth weight, and maternal height are predictors of stunting in <2 years toddlers. Objective: To analyze the stunting risk factors in toddlers in Majene Regency, West Sulawesi. Method: The case-control research design was employed for 58 cases and 58 control samples. The measurement of protein and zinc intake was completed by using a 24-hour food recall form, and the birth weight and height of the mother were obtained by using a questionnaire. The data were analyzed using odd ratio and logistic regression. Result: Those with less protein intake have a 3.34 times higher risk of stunting, while those with less zinc intake have a 34.46 times higher risk of stunting. Those with LBW history have a 2.12 higher risk of stunting but are not significant. Those whose mothers with short maternal height history have a 1.85 times higher risk of stunting but are not significant. Based on multivariate analysis, zinc intake is a risk factor for stunting (OR = 0.029 95% CI: 0.006-0.130). Conclusion: Protein intake, zinc intake, low birth weight, and maternal height history are risk factors for stunting occurrences.